الجوائز المادية مقابل الخدمات المصرفية بنك قطر الوطني الإسلامِي أنموذجاً : دراسة فقهية تطبيقية - شمري، نايف نهار (Kulliyat Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah Maliziya, 2012)
This thesis deals with the issue of valuable prizes provided by QNB Al-Islami to its customers in terms of their association with banking services. This includes giving non-usurious loans to anyone who opens a current account, or prizes related to credit cards. Initially the problem does not originate in the ruling of these prizes nor in the ruling of banking services but rather the dilemma lies in intertwining the two together, making the contract a complex one. It is known that contracts may be permissible in Islamic jurisprudence when they stand alone, but once one is added to another it may have a contrasting ruling. The issues of this study have been dealt by using a surveillance approach which is done by following the details of the issues as well as an analytical approach where the issues are realised, their realities and their obstacles clarified. Finally, this study applied a comparative approach by reviewing the statements of scholars of Islamic jurisprudence on these matters, understanding the intended meaning by referring to the original sources, discussing their evidences and their understandings of the evidences, and finally attempting to find a common ground between them. Also the study tries to verify the authentic sources of the hadeeths and state their validity according to their original sources and the verdicts of the scholars. This study concludes with numerous findings, some of which are: The default ruling regarding to prizes associated with current accounts is prohibited, because of the issue of taking advantage and benefit from a loan, unless the prize is not associated with any condition or any convention for loan based account. Nonetheless, the default ruling regarding prizes associated with savings accounts and investment deposits are permissible because the accounts are based on Mudharba, unless this leads to something non-permissible. As for prizes associated with credit cards, the ruling differs according to the type of credit card.